Perencanaan Komunikasi Event Ruang Visi Nusantara Bengkulu (Studi Pada Event “Linimasa Masanya Segala Lini”) - Sari, Melinda; Muwarni, Anis Endang Sri; Putra, Dilmai (Jurnal Multidisiplin Dehasen (MUDE), 2025)
An event organizer is a business that operates in the field of professional service provision. Event organizers assist with personal events such as weddings and birthdays, as well as other events. The type of research used by the researchers is descriptive qualitative. Data collection was carried out using observation techniques, interviews, and documentation techniques. The informants in this study consisted of several parties from RVN Management, including the Head of the Public Relations and Information Division, the Marketing Division, and the Event Manager. Based on field data, in the planning and implementation process of the concert " Linimasa Masanya Segala Lini," the researchers used the Cutlip & Center theory as research indicators, which includes four main stages: fact-finding, planning, communication, and evaluation. The results of the study showed that first, in the fact-finding stage, the RVN management team conducted surveys to determine the audience's enthusiasm for the invited artists. Second, in the planning stage, the RVN team planned and outlined the necessary steps to achieve the event's objectives, including selecting artists, assigning tasks to the committee team, and arranging vendors. Third, in the communication stage, RVN management utilized social media and influencers to convey the main message to the audience, which was to create a memorable experience for viewers. Fourth, in the evaluation stage, RVN management assessed the success of the concert not only through ticket sales but also through the experiences and comfort felt by the audience. Overall, the application of Cutlip & Center's communication planning theory in the " Linimasa Masanya Segala Lini" concert was systematically conducted. Each stage contributed significantly to the event's execution, although there were some shortcomings that need to be addressed.